EQUINE METABOLIC SYNDROME - Niedźwiedź, A.; Maksymovych, I.; Gutyj, B.; Slivinska, L.; Stronskyi, Y.; Leno, M.; Chernushkin, B.; Rusyn, V.; Leno, Y.; Karpovskyi, V.; et al. (Scientific Progress & Innovations, 2022)
The article defines the disease – the equine metabolic syndrome (EMS) and based on literature data, the leading causes, pathogenesis, diagnosis, prevention, and treatment of complications provoked by equine metabolic syndrome are described. Equine metabolic syndrome is registered in young horses and old animals. For example, Morgan, Paso Fino, Arabian, riding, and thoroughbred horses. Diagnosis of equine metabolic syndrome is based on the analysis of breed and genetic predisposition, determination of insulin resistance, and the degree of obesity. Early diagnosis of equine metabolic syndrome prevents the development of laminitis. Therefore, the primary treatment for equine metabolic syndrome is weight loss, with a combination of diet and exercise in horses without developing laminitis. Treatment and care of an animal with metabolic syndrome require an individual approach. The main strategic direction in solving the problem of insulin resistance should be based on weight loss and increasing insulin sensitivity by changing the diet and increasing physical activity. A change in diet is to reduce energy components and non-structural carbohydrates in its composition. In addition, grazing should be avoided, especially during the season when young, fresh grass appears. It is necessary to pay attention to the pastures, where today the number of grasses of genetically modified species, which are grown for milk production and fattening cattle, is increasing. Such grasses are characterized by a high content of NSC, which is the opposite of the pastures that are necessary for horses. Suppose the equine metabolic syndrome was established after the detection of laminitis. In that case, measures should reduce body weight, but with little physical activity, to not expose further damage to the hooves. Therefore, priority is directed to remove the animal from the laminitis and reduce obesity with significantly reduced physical activity. A low-carb diet should reduce insulin activity. However, if its activity is very high, you can use drugs to decline its level.